A Twisted Nanographene Consisting of 96 Carbon Atoms. (16th May 2017) - Cheung, Kwan Yin; Chan, Chi Kit; Liu, Zhifeng; Miao, Qian
Abstract: Herein we report synthesis, structure and properties of a new type of twisted nanographene, which contains an [8]circulene moiety in a polycyclic framework of 96 sp 2 carbon atoms. The key steps in this synthesis are the Diels–Alder reaction of a macrocyclic diyne and the subsequent Scholl reaction forming the [8]circulene moiety. Two incompletely cyclized products were isolated from the Scholl reaction, providing insight into the cyclization of the strained octagon. This nanographene is twisted along two directions with end‐to‐end twists of 142.4° and 140.2° as revealed by X‐ray crystallography, and is flexible at room temperature as found from the computational and experimental studies.